2013
DOI: 10.2807/1560-7917.es2013.18.37.20585
|View full text |Cite
|
Sign up to set email alerts
|

The test-negative design: validity, accuracy and precision of vaccine efficacy estimates compared to the gold standard of randomised placebo-controlled clinical trials

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
182
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 30 publications
3
182
1
Order By: Relevance
“…• Measured and compared VE of pandemic and seasonal vaccines in various seasons documenting variation across seasons and sometimes across vaccines within a season in studies where classical controls were not employed (45,72,73) • In a few studies where different control groups were compared, VE estimates were sometimes similar for the test-negative design (74) and sometimes different (75); a comparison of perprotocol results from RCTs versus estimates from test-negative observational studies of an influenza vaccine and of an RSV monoclonal antibody showed close concordance (26) .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…• Measured and compared VE of pandemic and seasonal vaccines in various seasons documenting variation across seasons and sometimes across vaccines within a season in studies where classical controls were not employed (45,72,73) • In a few studies where different control groups were compared, VE estimates were sometimes similar for the test-negative design (74) and sometimes different (75); a comparison of perprotocol results from RCTs versus estimates from test-negative observational studies of an influenza vaccine and of an RSV monoclonal antibody showed close concordance (26) .…”
Section: Discussionmentioning
confidence: 97%
“…As a corollary, the number of potential biases identified for a particular design is not an indicator of the design's desirability, as these biases may be of trivial magnitude in particular cases. Some work has been done, but more work is needed, to estimate the likely magnitude of these biases (26,27,41,(61)(62)(63). Such work is important because of the high reliance on such studies to provide of the evidence base used to set vaccine policy.. Failure to account for such biases has led to large errors in the estimates of vaccine effects in observational studies, and that these errors may be amplified as they gain authority and apparent precision through the process of systematic review and meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accuracy and validity of the TND design has been demonstrated, 38 although inherent bias and confounding factors still exist in this observational study design. In practice, small sample sizes leading to wide confidence intervals and lack of statistical power, particularly upon sample stratification, contribute to imprecise VE estimates.…”
Section: (I)variability Between Observational Studies Used To Calculamentioning
confidence: 99%